Descriptive Analysis of Cerebral Arterial Vascular Architecture in Dromedary Camel (Camelus dromedarius) - Al Aiyan, Ahmad; Menon, Preetha; AlDarwich, Adnan; Almuhairi, Fatema; Alnuaimi, Shaikha; Bulshawareb, Asma; Qablan, Moneeb; Shehab, Safa (Frontiers in Neuroanatomy, 2019)
The artiodactyl brain has multiple levels of vascular pooling and the rostral epidural rete mirabile (RERM) at its base. The current study is the first of its kind to precisely demonstrate the arterial vasculature of the dromedary brain, utilizing a new casting method with coloured latex and epoxy paint. In total, 35 freshly slaughtered dromedary heads were injected with coloured latex or coloured epoxy paint prior to dissection in order to reveal cerebral vasculature; Ten processed heads were chemically digested with 5% potassium hydroxide to obtain hard casts of cerebral arteries and anastomosing structures. The outcomes of this study ascertain the distinct vascular features of dromedaries that set them apart from other artiodactyls. In addition to the RERM, the dromedary possesses a well-developed ophthalmic and chiasmatic rete. The dromedary is similar to giraffe, goat, cat and pig in the contribution of middle meningeal artery to the rete mirabile; however, dromedaries have several arteries emerging directly from the cerebral arterial circle that supply the choroid plexus and pineal gland. Additionally, dromedaries exhibit a dominant basilar system that dominates the, blood supply to the medulla oblongata, pons, and cerebellum. In our study, we were able to graphically prove the lack of connection between the areas supplied by vertebrobasilar system and carotid system in the dromedary. Furthermore, the vertebral artery does not branch into the basilar artery; instead, it acts as a contributing vessel to the ventral spinal artery that later fuse to form the basilar artery. This study employed the new casting method to illustrate a new arterial source to RERM and the various anastomoses among arterial sources supplying the brain in the dromedary. These anastomoses play an important role in maintaining an uninterrupted cerebral blood supply, decreasing the vulnerability of the fragile brain against ischaemia and stroke, as well as, play an important role in maintaining blood pressure and flow in long-necked dromedaries when they raise or lower their heads.